The role of English in the internationalization of higher education in Vietnam - Vân, Hoàng Văn (VNU Journal of Foreign Studies, 2013)
Abstract: The aim of this paper is to discuss the role of English in the internationalisation of higher education inVietnam. The paper begins with exploring the concepts of “internationalization” and “globalisation” and discussing their impacts on higher education. Then it attempts to point out the opportunities internationalisation and globalization bring to the Vietnamese higher education and the challenges the Vietnamese higher education may experience as a result of internationalisation and globalisation. Having explored the above issues, the paper turns to a discussion of the roles of English in the internationalisation of higher education inVietnam. Then it takes a brief look at the current state of English language teaching and learning at Vietnamese tertiary level, presenting some false expectations concerning the required output level of English as a subject. In the concluding section, the paper argues that as internationalisation of higher education is becoming an inevitable tendency, English will have more roles to play inVietnam. This will call for a new vision for teaching and research, creating real needs for researchers, educational administrators, foreign language planners and English teachers to rethink of the roles of English in the development of higher education inVietnam so that English will become our real window to the world of science, technology and human intellectual essence. Keywords: internationalization, globalization, higher education, global language, false expectation